2005
DOI: 10.1242/dev.01966
|View full text |Cite
|
Sign up to set email alerts
|

Mammary ductal morphogenesis requires paracrine activation of stromal EGFR via ADAM17-dependent shedding of epithelial amphiregulin

Abstract: Development 132, 3923-3933.On p. 3924 of this article in the section 'Mammary organoid culture', the concentrations of three constituents in the basal medium are incorrect. The correct concentrations are 10 g/ml insulin, 5.5 g/ml transferrin and 5 ng/ml sodium selenite.In addition, the authors also wish to acknowledge Jimmie E. Fata for his suggestions regarding this assay.The authors apologise to readers for these mistakes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
230
3
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 265 publications
(246 citation statements)
references
References 64 publications
(67 reference statements)
12
230
3
1
Order By: Relevance
“…Nevertheless, the under-developed EGFR-null transplants still formed alveoli in response to prolactin from adjacent pituitary isografts, suggesting that EGFR was essential for ductal but not alveolar development. Similar recombination studies were later performed in the presence of slow-release estradiol pellets in order to also assess the role of EGFR in estrogen-induced alveolar differentiation, and once again, wild-type and EGFR-null epithelium grew in fat pads that contained EGFR, but not in EGFR-null fat pads [28]. And, as was true for pituitary prolactin, EGFR was not required for estrogen-induced alveolar expansion.…”
Section: Stromal Egfr Is Required For Mammary Developmentmentioning
confidence: 90%
See 1 more Smart Citation
“…Nevertheless, the under-developed EGFR-null transplants still formed alveoli in response to prolactin from adjacent pituitary isografts, suggesting that EGFR was essential for ductal but not alveolar development. Similar recombination studies were later performed in the presence of slow-release estradiol pellets in order to also assess the role of EGFR in estrogen-induced alveolar differentiation, and once again, wild-type and EGFR-null epithelium grew in fat pads that contained EGFR, but not in EGFR-null fat pads [28]. And, as was true for pituitary prolactin, EGFR was not required for estrogen-induced alveolar expansion.…”
Section: Stromal Egfr Is Required For Mammary Developmentmentioning
confidence: 90%
“…Although the above genetic evidence indicates that AREG is uniquely required for normal mammary morphogenesis [25], other studies had shown that several EGFR ligands could rescue ductal development in ovariectomized and ERα-deficient mice [26,[31][32][33] and that all EGFR ligands had comparable effects in culture [17,28]. So why were other EGFR agonists unable to compensate for the absence of AREG in vivo?…”
Section: Epithelial Areg Is Essential For Mammary Developmentmentioning
confidence: 99%
“…MMPs and the related families of proteinases, the ADAMs (a disintegrin and metalloproteases) and ADAM-TSs (ADAMs with thrombo spondin repeats), are important in shedding plasma-membrane-bound proteins. ADAMs and ADAM-TSs participate in shedding growth factors that are synthesized as cell-membrane-bound precursor forms, including heparin-binding epidermal growth factor (HB-EGF), neuregulin, amphiregulin and transforming growth factor-α (TGFα) [25][26][27][28] . Cleavage of other membrane proteins, such as Ecadherin and CD44, results in the release of specific, biologically active fragments of their extra cellular domains, and in increased invasive behaviour 29,30 .…”
Section: Functions Of Mmp Proteolysismentioning
confidence: 99%
“…• Epidermal-growth-factor receptor (EGFR) ligands need to be processed to function 28,[142][143][144] Cell survival…”
Section: Proliferationmentioning
confidence: 99%
“…Second, primary mammary glands can be cultured, infected with lentiviral or retroviral expression vectors, and transplanted back into wild-type mammary glands (Welm et al, 2005). Lastly, primary mammary organoids cultured in Matrigel can develop into highly branched structures in the presence of growth factors (Sternlicht et al, 2005). The organoids can be cultured with specific inhibitors or viral vectors for analysis of mammary branching.…”
Section: Transcription Factorsmentioning
confidence: 99%